Emotional Awareness and Internalizing Problems. A Preliminary Test of State and Trait Associations among Adolescents - Ghafaryan Shirazi, Yasaman; Lindblom, Jallu; Punamäki, Raija-Leena; Yli-Peltola, Marianna; Peltonen, Kirsi (European Journal of Mental Health, 2023)
Introduction: Difficulties in emotional awareness (EA) are often linked to the risk of internalizing problems (IP). Most empirical studies have found this association but have not considered possible state- and trait-related fluctuations in EA and IP assessments.Aims: We tested the directionality of the state-level associations, that is, whether EA at Time 1 predicts IP at Time 2 or the other way around. In line with previous research, we hypothesized that low EA would predict a subsequent increase in IP, as difficulties in emotional awareness dispose one to emotional problems. As an alternative model, we tested the trait-level associations between EA and IP. We hypothesized that a negative latent correlation exists between EA and IP, as common factors may cause them to be associated at the trait level.Methods: Participants were 68 students who completed the Levels of Emotional Awareness Scale and the Strength and Difficulties Questionnaire at two-time points with a one-month interval. We used the Cross-lagged Panel Model to test the state-level associations and structural equation modeling to test trait-level effects.Results: Results displayed no directional effect of EA on IP, and neither did IP predict EA within one month. However, we found a trait-level correlation between EA and IP. We discuss the preliminary results between state and trait level EA and IP in the context of the early developmental environment.Conclusions: This study is a preliminary test of state- and trait-level associations between EA and IP, which could be valuable for practitioners and clinicians.